2012
DOI: 10.1515/cclm-2012-0085
|View full text |Cite
|
Sign up to set email alerts
|

The new Roche Vitamin D Total assay: fit for its purpose?

Abstract: Background: Measurement of serum 25-hydroxyvitamin D [25(OH)D] is used to assess vitamin D status. We evaluated the analytical performance of a new automated assay, Elecsys Vitamin D Total (Roche Diagnostics, Mannheim, Germany), based on competitive protein binding. Methods: The Elecsys assay was tested for imprecision, linearity and functional sensitivity at three test-sites and compared to a liquid chromatography-tandem mass spectrometry (LC-MS/MS) method, a high-performance liquid chromatography (HPLC) meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 0 publications
0
16
1
Order By: Relevance
“…Recent study of imprecision test for Elecsys assay showed that it correlated well with LC-MS/MS (r = 0.93), HPLC (r = 0.91), and the Liaison assay (r = 0.86), indicating an excellent agreement. 16 In light of this close agreement, it appears unlikely that different methods of VD measurement affect the main findings of these studies. The third limitation is that most studies were performed in one single center; negative findings in our study therefore highlighted a new insight that results may vary in different populations and settings.…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…Recent study of imprecision test for Elecsys assay showed that it correlated well with LC-MS/MS (r = 0.93), HPLC (r = 0.91), and the Liaison assay (r = 0.86), indicating an excellent agreement. 16 In light of this close agreement, it appears unlikely that different methods of VD measurement affect the main findings of these studies. The third limitation is that most studies were performed in one single center; negative findings in our study therefore highlighted a new insight that results may vary in different populations and settings.…”
Section: Discussionmentioning
confidence: 71%
“…Serum levels of 25(OH)D were measured using an automated electrochemiluminescence-based assay, Elecsys Vitamin D Total (Roche Diagnostics, Mannheim, Germany). 16 The data are expressed as nanograms per milliliter. 25(OH)D concentrations < 20 and < 30 ng/mL were defined as deficiency and insufficiency, respectively, while concentrations ≥ 30 ng/mL were considered to indicate sufficient VD.…”
Section: Methodsmentioning
confidence: 99%
“…25(OH)D was measured in the serum of every participating patient, using Elecsys â Vitamin D total assay by Roche Diagnostics, an electro-chemiluminescence binding assay, as previously described. 16…”
Section: Participantsmentioning
confidence: 99%
“…The Elecsys Total 25-hydroxyvitamin D assay (Roche Diagnostics GmbH, Germany) was used for the quantative determination of total serum 25-hydroxyvitamin D (25(OH)D) (nmol/L) [34]. Intra-assay coefficient of variation was <10%.…”
Section: Vitamin D Statusmentioning
confidence: 99%